Competency of Successful Professional Trainers in Thailand in the Disruption Era (Journal of Organizational Psychology, 2024)
Current disruption era necessitates ongoing skill development for HR through training. Competency of professional trainers is key to training success. In-depth interviews with training managers, professional trainers, and training attendees revealed three components of competency - traits, knowledge, and skills. Traits comprised attitude (i.e., great heart and growth) and personality (i.e., passionate, accessibility, signature, and suitable to audience). Knowledge comprised expertise (i.e., content expertise and company/industry expertise) and experience (i.e., work experience and life experience). Skills comprised learning design skills (i.e., application of appropriate techniques and stakeholder-centered design), delivery skills (i.e., application-oriented and persuasive and inspiring), and developing business skills/entrepreneurship.
Keywords: organizational psychology; professional trainer; corporate trainer; successful trainer; competency; soft skills training; disruption era